Life Experiences of Borderline Personality Disorder Survivors in the Recovery Process: A Qualitative Study - Endah Sarwendah Sarwendah; Suryani Suryani; Efri Widianti (JKP (Jurnal Keperawatan Padjajaran), 2022)
Background: Borderline Personality Disorder or BPD is a personality disorder with the main symptoms are emotional instability, impulsive behavior, negative self-concept, and impaired interpersonal function. Recovery in BPD is directed at the existence of satisfaction and meaning in life even with limited conditions due to symptoms of the disorder that still exists.